2013
DOI: 10.1016/j.enpol.2012.08.073
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and energy policy in Chile: Up in smoke?

Abstract: This paper provides an ex-post assessment of the climate and energy policy developments in Chile emerging from a neoliberal economic model, during the period 1971-2007. First, correlation and regression analyses were performed to analyse historical CO 2 emissions as a product of demographic, economic and energy-wide drivers. Then I estimate indicators related to CO 2 emissions, energy use and economic activity. In the light of empirical results, I identify policy instruments and structural issues. Finally, I p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 23 publications
1
12
0
2
Order By: Relevance
“…Emissions grew faster than both GDP and energy use, which grew at nearly twice their average historical rates. The consequent increase in carbon and energy intensity confirms the historical lack of progress in energy efficiency and decarbonisation across LATAM (Mundaca, 2013). The CO 2 content of the energy supply mix increased by 1.7%, and was the highest growth rate across all regions.…”
Section: Resultsmentioning
confidence: 60%
“…Emissions grew faster than both GDP and energy use, which grew at nearly twice their average historical rates. The consequent increase in carbon and energy intensity confirms the historical lack of progress in energy efficiency and decarbonisation across LATAM (Mundaca, 2013). The CO 2 content of the energy supply mix increased by 1.7%, and was the highest growth rate across all regions.…”
Section: Resultsmentioning
confidence: 60%
“…However, there is some controversy regarding the term. [13] prefers to move away from the concept of 'decoupling' mentioned above, which is often used to refer to the situation where resources impact on the decline relative to GDP growth. The author pointed out that the term decoupling has been used as a key political element to bridge the contentious debate on continuous economic growth and its negative impact on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…If the aim is to reduce air pollution due to wood-fuel combustion, we must also concentrate efforts upon the sectors with the greatest annual consumption; that is, home owners who already have improved modern equipment as well as access to dry wood-fuel. The striking difference in house values suggest that it is very likely that the higher consumption is due to higher incomes, in agreement with increased energy-use driven by affluence (Mundaca, 2013). These facts are strongly associated with poor thermal insulation in buildings: if affluence does not reach building quality, then higher comfort is satisfied with higher energy consumption.…”
Section: House-value Dependence Of Firewood and Wood-stove Qualitymentioning
confidence: 87%
“…A sharp and steady increase in Gross Domestic Product (GDP) since 1990 was paralleled with a 320% increase in energy use between 1990 and 2007. Much related to energy use, Mundaca (2013) showed that the increase in CO 2 emissions is explained by the increase in GDP per capita, i.e. affluence, rather than population or total GDP growth.…”
Section: Air Pollution and Wood-fuel Consumptionmentioning
confidence: 99%